Modulação da atividade dos canais de sódio dependentes de voltagem e de canais TRPV1 por (-)-Carvona - Gonçalves, Juan Carlos Ramos (2011)
Among the natural products with experimentally proven analgesic properties, the monoterpernes are of great importance, recognized as the main chemical constituents of essential oils from aromatic plants. ( )-Carvone is an example of monoterpene with antinociceptive properties, founded as the main active constituent of oils from some species of the genus Mentha. Since the peripheral antinociceptive mechanism of ( )-carvone is not well established, this study aimed to better characterize it. Initially, it was performed a structure-activity study by which was possible to demonstrate the importance of the carbonyl group into the molecule of ( )-carvone, during its blocking effect in the rat peripheral nervous excitability, as also that the replacement of that group for a hydroxyl enhanceed this effect. After shown that ( )-carvone had low cytotoxicity, we investigated the effects of this monoterpene in the voltage-gated sodium channels of (Nav) and the transient receptor potential vanilloid 1 (TRPV1), involved in peripheral nociception, using neurons from the dorsal root ganglion (DRG) of rats. With the technique of Whole-cell Patch-clamp it was demonstrated that ( )-carvone (1 mM) was able to reduce Na+ influx from 8.7±1.6 nA (control) to 5.3±1.1 nA (p <0.05). Later, by fluorescence microscopy assays, we observed that ( )-carvone increased the Ca2+ levels in DRG neurons, possibly via TRPV1 channels. The involvement of these channels was further confirmed by specific antagonism and heterologous expression in HEK 293 by transfecting these cells with TRPV1-cDNA of Rattus novergicus. Then we demonstrated that ( )-carvone acts in the TRPV1 channel in a concentration-dependent manner, promoting its desensitization. Additionally, it was discarded the participation of another TRP channel involved in pain, the TRPM2, during the effect of ( )-carvone. Therefore, this study showed that the replacement of a carbonyl by a hydroxyl group in the molecule of ( )-carvone could increase the efficiency of this monoterpene in reducing the peripheral nerve excitability. Such effect was demonstrated as being a result of the Nav channel blockade, as well as the activation and subsequent desensitization of TRPV1 channels, indicating the great potential of this monoterpene as a peripheral antinociceptive molecule or prototype of a novel analgesic drug.